Towards statistically literate communication professionals - Silvestre, Cláudia (2017)
Communication professionals increasingly need to be able to read and critically comment on statistical data to communicate statistical information fittingly. Consequently, Statistics play an important role in the education of these professionals. Unfortunately, in Portugal most of the students who intend to become communication professionals do not feel at ease with numbers, mathematics or statistics. To engage our students and motivate them to learn, we have selected working groups themes related to their courses and used statistical information available in the real world. With this approach, we expect to get students more involved, make them familiar with using statistical information and let them increase their statistical skills. Therefore, everybody in the classroom, both students and teachers, are likely to become more motivated.